Methionyl-tRNA synthetase synthetic and proofreading activities are determinants of antibiotic persistence - Wood, Whitney N.; Rubio, Miguel Angel; Leiva, Lorenzo Eugenio; Phillips, Gregory J.; Ibba, Michael (Frontiers in Microbiology, 2024)
Bacterial antibiotic persistence is a phenomenon where bacteria are exposed to an antibiotic and the majority of the population dies while a small subset enters a low metabolic, persistent, state and are able to survive. Once the antibiotic is removed the persistent population can resuscitate and continue growing. Several different molecular mechanisms and pathways have been implicated in this phenomenon. A common mechanism that may underly bacterial antibiotic persistence is perturbations in protein synthesis. To investigate this mechanism, we characterized four distinct metG mutants for their ability to increase antibiotic persistence. Two metG mutants encode changes near the catalytic site of MetRS and the other two mutants changes near the anticodon binding domain. Mutations in metG are of particular interest because MetRS is responsible for aminoacylating both initiator tRNA Met and elongator tRNA Met indicating that these mutants could impact translation initiation and/or translation elongation. We observed that all the metG mutants increased the level of antibiotic persistence as did reduced transcription levels of wild type metG. Although, the MetRS variants did not have an impact on MetRS activity itself, they did reduce translation rates. It was also observed that the MetRS variants affected the proofreading mechanism for homocysteine and that these mutants' growth is hypersensitive to homocysteine. Taken together with previous findings, our data indicate that both reductions in cellular Met-tRNA Met synthetic capacity and reduced proofreading of homocysteine by MetRS variants are positive determinants for bacterial antibiotic persistence.